Estrategias heurísticas en la mejora de resolución de problemas de cantidad en estudiantes de segundo grado de secundaria de la Institución Educativa 601057 Bilingue Intercultural del Yavarí 2025 - Escalante Huanaco, Joel (2025)
The study aimed to evaluate the effect of heuristic strategies on improving the ability of second-year secondary school students (grades 601057) to solve quantitative problems. An applied research approach with a pre-experimental design (pretest and posttest) was used, employing a census sample of 22 students. The instrument was a 20-item questionnaire, and the data were analyzed using the Shapiro-Wilk normality test and the paired-samples t-test. The results showed significant improvements in student achievement levels: the "Beginning" level decreased from 77,3% to 0%, while the "Expected Achievement" and "Outstanding Achievement" levels increased to 40,9% and 9.1%, respectively. Significant differences were also found in the dimensions of translating quantities, communicating understanding, using calculation strategies and procedures, and arguing numerical relationships, all with p=0.001, confirming the pedagogical effectiveness of the applied strategies. It is concluded that the systematic use of strategies improves students' logical mathematical thinking in rural areas, strengthens their ability to formulate and solve mathematical problems, and contributes to meaningful and sustainable learning.